BIOCHEMICAL INDICATORS OF SOYBEAN’S DRAUGHT-RESISTANCE - Li , T.; Didorenko , S.; Orazbayeva , U.; Spankulova , Z.; Tashkenova , A.; Birimzhanova , Z. (Eurasian Journal of Applied Biotechnology, 2013)
Soybean is the most important legumes in the world and an important source of protein, oil, macro-and micronutrients. Despite the increase in world demand for cultural soya as a source of vegetable protein and oil, the current losses in the production of soybean comprise over one fifth crop worldwide. Аbiotic stress factors are responsible for most of these losses of soybean yield compared with the maximum. In this regard, the study of drought tolerance and productivity of major agricultural crops, such as soybean, is a priority for Kazakhstan today. Our previous study of the antioxidant enzymes had revealed that the genotypes of wheat, developing a higher enzyme activity under stress, are proved to be more resistant to drought stress. We have studied the cultivated soybean Glycine max L. of the world collection, according to the preliminary data having traits of drought resistance: vr.Ustya (Ukraine), K589109 (Russia), K583583 HMAS 84 (USA) and related to early maturing group with vegetation period of 85-95 days. As the standard was used a variety of domestic breeding - Almaty. In the present research we applied the methods - determination of relative water content (RWC), determination of proline, detection of changes in the activity of antioxidant enzymes peroxidase (POD) and superoxide dismutase (SOD), phenological observations and analysis of the main elements of yield structure of contrasting soybean varieties. Development of a method for early diagnosis of drought resistance in legume crops, based on the screening of physiological and biochemical indicators of stress tolerance, is essential for accelerated breeding of soybean genotypes.